Hard labour? academic work and the changing landscape of higher education - Fitzgerald, Tanya, 1960-; White, Julie; Gunter, Helen M. (International perspectives on higher education research ;, 2012)
Higher education institutions (HEIs) have experienced massive changes in the past three decades. Across England, the US, Australia and New Zealand, new public management has introduced corporate governance structures, strategic plans, performance management, quality assurance processes, a client-focused approach to students and curriculum, and a commodification of higher education that has seen an unprecedented growth in international student numbers. Increased numbers of HEIs has stimulated a variety of challenges for administrators, academics, students and the broader community. Drawing on data from England, Australia and New Zealand, this book addresses how policies of successive labour governments have decreased autonomy of academics and increased regimes of surveillance, radically altering how academics think about and engage in their intellectual work. It provokes the reader to think critically about the emergence of corporate styles of governance, management and leadership in HEIs and ways in which the demands of new public management and the knowledge economy has shaped and re-shaped scholarly work and identity.